ANALISIS STRATEGI PEMASARAN DENGAN PENDEKATAN SWOT DAN QUATITATIVE STRATEGIC PLANNING MATRIX (QSPM) DALAM MENINGKATKAN PENJUALAN PADA PERCETAKAN MAXX DESIGN JEMBER - Faisol, Ahmad; Sumowo, Seno; Wibowo, Yohanes Gunawan (Growth, 2024)
This research aims to find out the right marketing strategy to increase sales at Maxx Design Jember. This type of research uses descriptive qualitative research. The sampling technique used Non Probability Sampling totaling 115 samples. Data collection techniques use interviews, observation, documentation and questionnaires. Data analysis techniques use SWOT and QSPM analysis. Based on the results of the research and discussion, it can be concluded that in the Cartesian SWOT diagram, Maxx Design Jember is at the coordinate point S;T = 0.27; -0.1, namely being in quadrant IV diversification, which is a strategy that focuses on strengthening the main business or creating supporting resources. Maxx Design Jember can use other social media information technology, not only YouTube, Instagram and Facebook. Using the marketplace as a new step to expand market share. Utilizing paid advertising on social media or using influencer services to promote products, and starting to use websites can be done even though it increases promotional costs, but this can be included as an investment. Because the impact of this promotional strategy will affect the development and sales of the product it self.